At the Margins of Epistemology: Amplifying Alternative Ways of Knowing in Library and Information Science. Issue 1 (13th October 2021) - Patin, Beth; Oliphant, Tami; Allard, Danielle; Gray, LaVerne; Clarke, Rachel Ivy; Tacheva, Jasmina; Lar‐Son, Kayla
Abstract: This panel argues a paradigm shift is needed in library and information science (LIS) to move the field toward information equity, inclusion, relevance, diversity, and justice. LIS has undermined knowledge systems falling outside of Western traditions. While the foundations of LIS are based on epistemological concerns, the field has neglected to treat people as epistemic agents who are embedded in cultures, social relations and identities, and knowledge systems that inform and shape their interactions with data, information, and knowledge as well as our perceptions of each other as knowers. To achieve this shift we examine epistemicide—the killing, silencing, annihilation, or devaluing of a knowledge system, epistemic injustice and a critique of the user‐centered paradigm. We present alternative epistemologies for LIS: critical consciousness, Black feminism, and design epistemology and discuss these in practice: community generated knowledges as sites of resistance and Indigenous data sovereignty and the "right to know".